Lev Vygostky between psychology, linguistics and semiotics - Velmezova, Ekaterina (Rivista Italiana di Filosofia del Linguaggio, 2005)
Even if L.S. Vygotsky (1896-1934) is known first of all for his research in the domain of developmental and cultural-historical psychology, his rich intellectual heritage allows his works to be studied from different points of view by specialists in various fields of knowledge (psychologists and philosophers, semioticians, linguists and anthropologists…). The many conferences about Vygotsky organized all over the world and increasing research on various aspects of his works bear witness to the growing interest in his theories. They contribute to the development of «vygotskology» [vygotskovedenie] as a particular branch of the humanities which is situated at the intersection of several domains of knowledge.